ANALISIS PEMERIKSAAN IVA TEST PADA WANITA USIA SUBUR DI BPM SUPADMI, SST, M.Si DESA KUNDEN, BULU, SUKOHARJO - N. Kadek Sri Eka Putri; Hastutik - (Jurnal Ilmiah Maternal, 2017)
ABSTRACT Cervical cancer can be prevented and treated if found / detected at an early stage. WHO recommends that all women do are sexual active to perform early detection because the  suc- cessfully key of cancer control programs is on effective screening and early treatment. Early screening method of cervical cancer can be done through Pap Smear Test and Visual Inspection with Acetic Acid (IVA). IVA is a new of early detection method of cervical cancer by applying acetic acid (vinegar) into the cervix. If there is a cancer lesion, there will be a slight white dis- coloration on the cervix was examined. The purpose of this study was to analyze the IVA Test in women at fertility age in BPM Supadmi, SST, M.Si Kunden Village, Bulu, Sukoharjo. The research used descriptive research method with retrospective approach, conducted in BPM Supadmi, SST, M.Si at January - June 2017. Population of the research was mothers conduct- ing IVA test at BPM Supadmi, SST, M.Si , From January to June 2017 with a sample saturated technique of 81 respondents. The instrument used is secondary data by register IVA test exami- nation in BPM Supadmi, SST, M. Si. The results showed that most respondents aged 31-70 years was 62 respondents (76.5%), while respondents aged 21-30 years a number was 19 respondents (23.5%). IVA examination Test with negative result counted 71 respondents (87.7%) and re- spondents with positive results of IVA test counted 10 respondents (12.3%). The conclusion that can be obtained by the examination of IVA Test with negative result as much as 71 respondents (87.7%) and positive test counted 10 respondents (12.3%). Keywords: IVA Test Examination, Female at Fertility Age  ABSTRAK Kanker serviks dapat dicegah dan diobati jika ditemukan/dideteksi pada stadium dini. WHO merekomendasikan seluruh wanita yang aktif berhubungan seks untuk melakukan deteksi dini karena kunci keberhasilan program pengendalian kanker adalah pada penapisan yang efektif dan penanganan sedini mungkin. Metode skrining dini kanker serviks dapat dilakukan melalui Tes Pap Smear dan Inspeksi Visual dengan asam asetat (IVA). IVA adalah metode baru deteksi dini kanker leher rahim dengan mengoleskan asam asetat (cuka) ke dalam leher rahim. Bila terdapat lesi kanker, maka akan terjadi perubahan warna menjadi agak keputihan pada leher rahim yang diperiksa. Tujuan dari penelitian ini untuk menganalisa pemeriksaan IVA Test pada wanita usia subur di BPM Supadmi, SST, M.Si Desa Kunden, Bulu, Sukoharjo. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian diskriptif denganpendekatan retrospektif, dilaksanakan di di BPM Supadmi, SST, M. Si mulai dari Bulan Janu- ari - Juni 2017. Populasi penelitian ibu-ibu yang melakukan pemeriksaan IVA test di BPM Su- padmi, SST, M.Si mulai dari Bulan Januari - Juni 2017 dengan teknik sampel jenuh sebanyak81 responden. Instrumen yang digunakan adalah data sekunder register pemeriksaan IVA test di BPM Supadmi, SST, M.Si. Hasil penelitian menunjukkan bahwa sebagian besar responden berusia 31 – 70 tahun sejumlah 62 responden (76.5%), sedangkan responden yang berusia 21 –30 tahun sejumlah 19 responden (23.5%). Pemeriksaan IVA Test dengan hasil negatif sebanyak71 responden (87.7%) dan responden dengan hasil pemeriksaan IVA Test positif sebanyak 10 responden (12.3%). Simpulan yang dapat diperoleh yaitu Pemeriksaan IVA Test dengan hasil negatif sebanyak 71 responden (87.7%) dan responden dengan hasil pemeriksaan IVA Test positif sebanyak 10 responden (12.3%). Kata kunci: Pemeriksaan IVA Test, Wanita Usia Subur